2021
DOI: 10.3390/ma14175073
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Embrittlement of the Additively Manufactured High-Strength X3NiCoMoTi 18-9-5 Maraging Steel

Abstract: The main aim of this study was to determine the susceptibility of the additively manufactured high strength X3NiCoMoTi 18-9-5 maraging steel to hydrogen embrittlement. For this purpose, samples produced by selective laser melting technology, before and after heat treatment, were used. The examined samples were electrochemically charged with hydrogen in NaCl + NH4SCN solution at a current density of 50 mA/cm2 for 24 h. The H content increased from about 1 to 15 ppm. Heat treatment did not affect the amount of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Li et al suggested that H decreases the critical stress needed for martensitic transformation of retained austenite in L-PBFed 300 steel, leading to premature phase transformation and higher HE susceptibility. Similarly, Strakosova et al reported substantial HE in L-PBFed X3NiCoMoTi 18-9-5 maraging steel with a fully martensitic microstructure after heat treatment, H trapping at defects was suspected to be the main cause. HE of a 18Ni-300 maraging steel produced by SLM was also attributed to H trapping, in particular due to retained austenite.…”
Section: Knowledge Base About Hementioning
confidence: 90%
“…Li et al suggested that H decreases the critical stress needed for martensitic transformation of retained austenite in L-PBFed 300 steel, leading to premature phase transformation and higher HE susceptibility. Similarly, Strakosova et al reported substantial HE in L-PBFed X3NiCoMoTi 18-9-5 maraging steel with a fully martensitic microstructure after heat treatment, H trapping at defects was suspected to be the main cause. HE of a 18Ni-300 maraging steel produced by SLM was also attributed to H trapping, in particular due to retained austenite.…”
Section: Knowledge Base About Hementioning
confidence: 90%
“…More recently, the research on this topic has extended to additively manufactured bulk materials, e.g. see [28], [29] and [30]. There exist two prevailing theories for hydrogen embrittlement, namely the hydrogen enhanced decohesion (HEDE) mechanism and the hydrogen enhanced localized plasticity (HELP) mechanism.…”
Section: Introductionmentioning
confidence: 99%